1992
DOI: 10.1163/156856292x00178
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature incorporation of bovine serum albumin into a bead formed macroporous hydrophilic polymer matrix with potential for sustained release

Abstract: A process of freeze-thaw polymerization involving the low temperature photopolymerization of a mixed solution of monomers and bovine serum albumin around frozen ice crystals has been used to generate a bead formed macroporous hydrophilic matrix with potential for sustained release. Beads over the size range 100-3000 microns were fabricated with surface and internal pores of between 0.7-2.6 microns whose diameter could be controlled by manipulation of the monomers to solvent ratio. Increasing both the proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…On the other hand, ultrastructural examination of GOx loaded beads fabricated in the present study using freeze-thaw photopolymerization [14] confirmed that the initial burst release profile (Fig. 1) was not a function of the excessive outer-surface deposition of GOx during fabrication (Fig.…”
Section: Effect Of Bead Size On Glucose Oxidase and Il-2 Releasesupporting
confidence: 69%
See 4 more Smart Citations
“…On the other hand, ultrastructural examination of GOx loaded beads fabricated in the present study using freeze-thaw photopolymerization [14] confirmed that the initial burst release profile (Fig. 1) was not a function of the excessive outer-surface deposition of GOx during fabrication (Fig.…”
Section: Effect Of Bead Size On Glucose Oxidase and Il-2 Releasesupporting
confidence: 69%
“…The largest proportion of beads separated in the S00-1000,um size range and the mean total bead yield expressed as a percentage of the total weight of monomers used was 76.8 ± 3.8% (n = 10). The mean equilibrium buffer (sodium acetate/sodium chloride buffer, pH 7.4) content (EBC) of unloaded p-HEMA beads, expressed as a percentage of the weight of buffer within a bead sample at room temperature and controlled humidity [16] was 71.7 ± 0.92% (n = 15) compared with an EWC value for unloaded p-HEMA beads of 60.0±0.15% (n = 15), [14] (see Fig. 3).…”
Section: -mentioning
confidence: 97%
See 3 more Smart Citations